Tumour-draining axillary lymph nodes in patients with large and locally advanced breast cancers undergoing neoadjuvant chemotherapy (NAC): the crucial contribution of immune cells (effector, regulatory) and cytokines (TH1, TH2) to immune-mediated tumour cell death induced by NAC - Kaewkangsadan, Viriya; Verma, Chandan; Eremin, Jennifer M.; Cowley, Gerard P.; Ilyas, Mohammad; Eremin, Oleg (BioMed Central, 2018)
Background